Conservative treatment for pyogenic flexor tenosynovitis: a single institution experience. Issue 1 (2nd January 2020) - Frenkel Rutenberg, Tal; Velkes, Steven; Sidon, Eliezer; Paz, Lior; Peylan, Jacques; Shemesh, Shai; Iordache, Sorin Daniel
Abstract: Pyogenic flexor tenosynovitis (PFT) of the hand is a common infection which is clinically diagnosed using Kanavel's signs. Delay in diagnosis and treatment may lead to devastating outcomes, including reduced range of motion (ROM), deformities, tendon impairment or even amputation. While the gold standard for treatment is irrigation and debridement of the flexor sheath, little is known about the outcomes of conservative treatment with intravenous (IV) antibiotics. Patients treated conservatively for PFT between 2000 and 2013 were included. Demographic information, co-morbidities and clinical features at presentation such as Kanavel's signs and inflammatory markers levels were gathered. Treatment course, length of stay (LOS), functional outcomes and complications were collected. Fifty-four (54) patients presented with PFT in the study period. Forty-six (46) patients, ages 19–84 years old, who were treated conservatively were included. Average time from symptoms onset to presentation was 4.6 ± 7.1 days. Fourteen (14) patients failed to improve with course of oral antibiotics prior to presentation. The average number of Kanavel's signs was 3 ± 0.7. Inflammatory markers were elevated in 82.2% of patients. The mean LOS was 4.7 ± 2 days. Forty-four (44) patients continued follow-up for 55 ± 45 months. Final flexion ROM was full or minimally limited in 69% of patients. Three patients were eventually operated. Complication rate for the entire cohort was 4.3% and no fingers were lost. This retrospective case series indicate that inpatient empirical IV antibiotic therapy can be considered for patients presenting with uncomplicated PFT, provided it is practiced under a hand specialist's surveillance.